How women’s empowerment affects farm production and dietary quality in East Africa - Chege, Christine Gacheri Kiria; Onyango, Kevin; Muange, Elijah N.; Jäger, Matthias (2021)
Malnutrition remains a key global challenge constraining social and economic development in most developing countries. Although women can play an important role in improving household diet quality, their participation is constrained by limited access to productive resources. Women’s empowerment in agriculture is a viable strategy for improving dietary quality, but investigations on the important type(s) of empowerment are inconclusive. Using crosssectional data collected from Uganda and Kenya, and analyzed using three-stage least squares, this paper investigates women’s empowerment and its effect on dietary diversity. Women’s empowerment is measured using the Women’s Empowerment in Agriculture Index (WEAI). We find that control over use of income, autonomy in production and inadequate leisure time, are the major WEAI indicators contributing to women’s disempowerment. Regression analysis shows that farm production diversity positively influences dietary diversity, but only the production autonomy indicator has a positive and significant effect on farm production diversity, implying that women’s empowerment has an indirect positive effect on dietary diversity – through the farm production diversity pathway. Study implications are also explained.